Effect of citric acid supplementation on growth performance, carcass characteristics and physico-chemical attributes of male Venda chickens - Mamabolo, Matabo Vinolia (My University, 2023)
Two experiments were conducted to investigate the effect of citric acid supplementation on growth performance, carcass and physicochemical features of male Venda chickens. Day-old chicks were vaccinated against diseases at hatchery. Sick chickens were isolated and treated accordingly by the veterinarian. On Experiment 1, birds were assigned to four dietary supplemented with varying inclusion levels of citric acid. Treatment description was as follows: CA1: 0g/kg DM of feed, CA2: 12.5g/kg DM of feed, CA3: 25g/kg DM of feed, and CA4: 50g/kg DM of feed, where 50 chicks were randomly assigned to each treatment. In the present study, citric acid did not affect (P>0.05) DM feed intake and feed conversion ratio of male Venda chickens aged one to 30 days. However, citric acid supplementation affected (P<0.05) growth rate and live weights of male Venda chickens aged one to 30 days. The growth rates and live weights of male Venda chickens aged one to 30 days were optimised at citric acid supplementation levels of 2.392 and 2.536g per kg DM of the diet. Citric acid supplementation levels of 12 and 25g per kg DM improved (P<0.05) DM feed intake, growth rate, feed conversion ratio, and live weight of male Venda chickens aged 31 to 90 days. Optimal growth rate, feed conversion ratio, and live weights of male Venda chickens aged 31 to 60 days were optimised at citric acid supplementation levels of 2.250, 2.373, and 2.308g per kg DM of the diet. Citric acid supplementation levels of 1.560, 2.167, 2.332, and 2.272g per kg DM of the diet resulted in optimised DM feed intake, growth rate, feed conversion ratio, and live weights of male Venda chickens aged 61 to 90 days. Citric acid supplementation improved (P<0.05) live weight, carcass weight and dressing pieces of male Venda chickens aged 90 days. On experiment 2, the effect of citric acid supplementation on meat pH, thawing loss, cooking loss and shear force of male Venda chickens were determined. Supplementing Venda chickens with citric acid had affected (P<0.05) cooking loss, shear force and meat pH of male Venda chickens aged 90 days. Male chickens supplemented with 50g of citric acid per kg DM outperformed 0, 12.5 and 25g of citric acid per kg DM in terms of physicochemical features, implying that 50g of citric acid v per kg DM can help improve meat pH, thawing loss, cooking loss and shear force values of male Venda chickens. It can be concluded that citric acid supplementation of 12.5, 25g per kg DM can be utilized in the diet of Venda chickens aged one to 90 days. However, 50g of citric acid resulted in lower feed intake and weight loss this might be because high levels of citric acid supplementation may be too sour and made the feed to appear unappealing to the chickens. However, more research is needed to confirm these findings.
Thesis (M.Sc. (Animal Production)) -- University of Limpopo, 2023
Keywords: Citric acid; weights; Meat pH; Cooking loss; Chickens.; Citric acid; Chickens -- Feeding and feeds